Total fatigue life prediction of TC4 titanium alloy based on surface notch. (January 2022) - Ding, Mingchao; Zhang, Yuanliang; Li, Bo; Sun, Chengzhi; Lu, Huitian; Liu, Weiwei
Highlights: A total fatigue life separation model based on surface notch is studied. Neuber's rule shows a tendency of underestimating the notch-root strains of surface notch. The initial crack size a 0 for surface notch is established. Prediction results of the proposed model mainly falls into the scatter band of factor 1.5. Abstract: A surface notch will be produced in crack grinding process of cracked blade, and fatigue life of surface notch is a critical measure to assess its remanufacturability. In this paper, a total fatigue life separation model based on surface notch is studied, which is defined as the sum of crack initiation life and crack propagation life. Tensile fatigue experiments were performed on surface notched plate specimens. At a given notch depth, there is a negative correlation between the secondary crack density and the notch width. Combined with Neuber's rule and elastic–plastic finite element results, a residual thickness correction coefficient S ε is proposed to reflect the effect of finite thickness on local strain. Depending on simulation results, it is found that Neuber's rule underestimates the notch-root strains of surface notch, which is contrary to the current conclusions. Crack initiation life is estimated by modifying Morrow method with the proposed S ε . The initial crack size a 0 of surface notch is qualified by equivalent initial flaw size (EIFS) modified by fatigue strength calculated by Neuber approach. Crack initiation life is estimated by Labg equation with the improved a 0 . The proposed model is verified by fatigue experiment results with a prediction accuracy falling into the scatter band of factor 1.5. This study enriches the current notch fatigue analysis, which can provide reference suggestions by the model for crack grinding design in remanufacturing pre-treatment process.